Facile synthesis of porous spherical La0.8Sr0.2Mn1−xCuxO3 (0 ≤ x ≤ 0.4) and nanocubic La0.8Sr0.2MnO3 with high catalytic activity for CO. Issue 43 (23rd October 2018) - Huang, Xuehui; Pan, Hongyun; Chen, Kui; Yin, Zhilin; Hong, Jing
Abstract : A molten salt method has been used to prepare porous La0.8 Sr0.2 Mn1− x Cu x O3 (0 ≤ x ≤ 0.4) (LSMC- X ) microspheres and La0.8 Sr0.2 MnO3 (LSM) nanocubes using spherical and cubic MnCO3 as templates, respectively. Abstract : A molten salt method has been used to prepare porous La0.8 Sr0.2 Mn1− x Cu x O3 (0 ≤ x ≤ 0.4) (LSMC- X ) microspheres and La0.8 Sr0.2 MnO3 (LSM) nanocubes using spherical and cubic MnCO3 as templates, respectively. XRD patterns showed a single perovskite phase when the Cu content was less than x = 0.3. SEM and TEM images indicated that the porous microspheres comprised many aggregated nanoparticles, while the nanocubes were solid with a smooth surface. LSM and LSMC-0 samples both possessed high surface areas (63.5045 and 49.6504 m 2 g −1, respectively). Furthermore, the CO conversions showed that LSMC-0.2 had the best catalytic activity ( T 50 = 83.63 °C, T 90 = 97.40 °C) and good stability. XPS analysis confirmed that Cu 2+ doping induced Mn 4+ formation and slight changes in the oxygen species, leading to different catalytic activity. Owing to their facile synthesis and high catalytic performance, we propose that these porous spherical La0.8 Sr0.2 Mn1− x Cu x O3 (0 ≤ x ≤ 0.4) and nanocubic La0.8 Sr0.2 MnO3 catalysts are promising candidates for CO oxidation.